Improving Junior High School Students' Critical Thinking Through Scaffolding Methode on Heat Concept - Mahbubah, Khoiro; Santoso, Agus; Rosdiana, Silvi Rosiva; Djatmiko, Rahmad (KONSTAN - JURNAL FISIKA DAN PENDIDIKAN FISIKA, 2024)
Critical thinking helps students develop the ability to analyze information, search for evidence, and make decisions based on open and logical thinking. This study measures junior high school students' critical thinking on heat concepts by implementing the Scaffolding method. This research used a pre-experimental method with a one-group pre-test and post-test design with a quantitative approach. The subjects of this research were 57 seventh-grade students in junior high school. The results show that the paired sample t-test is 0.000 < 0.05, which shows that the Scaffolding method effectively improves students' critical thinking skills on heat concepts and is confirmed by the n-gain test of 0.73 in the high category. It can be concluded that the Scaffolding method effectively increases junior school students' critical thinking skills.